2014
DOI: 10.4269/ajtmh.13-0420
|View full text |Cite
|
Sign up to set email alerts
|

Encephalitis-Associated Hospitalizations among American Indians and Alaska Natives

Abstract: Abstract. Encephalitis produces considerable morbidity in the United States, but morbidity rates among American Indian/Alaska Native (AI/AN) people have not been described. Hospitalization records listing an encephalitis diagnosis were analyzed by using Indian Health Service direct/contract inpatient data. For 1998-2010, there were 436 encephalitisassociated hospitalizations among AI/AN people, an average annual age-adjusted hospitalization rate of 3.1/100,000 population. The rate for infants (11.9) was more t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…Following methodology from previous studies using IHS clinical data, the 12 IHS areas were collapsed into 7 standard administrative regions to limit attribution of study findings to individual tribes while still permitting analysis of regional variations. 22,23 The IHS regions (Figure A, available as a supplement to the online version of this article at http://www.ajph.org) incorporate the following administrative areas: East (Nashville), Northern Plains East (Bemidji), Northern Plains West (Great Plains, Billings), Alaska, Southern Plains (Oklahoma), Southwest (Albuquerque, Navajo, Phoenix— Tucson), and West (California, Portland). We excluded the West region from the inpatient and emergency department discharge data sets because of the lack of IHS- or tribally operated hospitals and emergency departments and the incompleteness of information on contract health services.…”
Section: Methodsmentioning
confidence: 99%
“…Following methodology from previous studies using IHS clinical data, the 12 IHS areas were collapsed into 7 standard administrative regions to limit attribution of study findings to individual tribes while still permitting analysis of regional variations. 22,23 The IHS regions (Figure A, available as a supplement to the online version of this article at http://www.ajph.org) incorporate the following administrative areas: East (Nashville), Northern Plains East (Bemidji), Northern Plains West (Great Plains, Billings), Alaska, Southern Plains (Oklahoma), Southwest (Albuquerque, Navajo, Phoenix— Tucson), and West (California, Portland). We excluded the West region from the inpatient and emergency department discharge data sets because of the lack of IHS- or tribally operated hospitals and emergency departments and the incompleteness of information on contract health services.…”
Section: Methodsmentioning
confidence: 99%
“…26,39,43,44 Globally, majority of studies have concluded that herpes simplex virus (HSV) is the most prevalent cause of VE. 4,12,25,43,[45][46][47][48][49][50][51][52][53][54][55][56] The pathogenic agents of VE vary from country to country. In Western countries such as France, England, and the United States, human simplex virus-1(HSV-1) has come up as the most prominent cause of sporadic VE.…”
Section: • Acute Ve • Postinfectious Encephalomyelitis • Slow Viral Imentioning
confidence: 99%